2017
DOI: 10.1007/jhep12(2017)105
|View full text |Cite
|
Sign up to set email alerts
|

Quark flavour-violating Higgs decays at the ILC

Abstract: Flavour-violating Higgs interactions are suppressed in the Standard Model such that their observation would be a clear sign of new physics. We investigate the prospects for detecting quark flavour-violating Higgs decays in the clean ILC environment. Concentrating on the decay to a bottom and a light quark j, we identify the dominant Standard Model background channels as coming from hadronic Standard Model Higgs decays with mis-identified jets. Therefore, good flavour tagging capabilities are essential to keep … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…So far, LHC has measured couplings with fermions of the 3rd generation, and there is some chance to measure couplings with charm and muons, which will permit to test the private Higgs hypothesis. At linear colliders it will be possible to measure these couplings with better precision; more recently there have appeared some claims that the coupling with strange quarks is also possible, both the flavor-conserving [139] and flavor-violating ones [140]. Furthermore, this could also be possible within the models with Higgs portal to dark matter, In such case, the direct detection of DM depends on the Higgs interaction with nucleons, which in turn depends on the Higgs coupling with light quarks.…”
Section: Discussionmentioning
confidence: 99%
“…So far, LHC has measured couplings with fermions of the 3rd generation, and there is some chance to measure couplings with charm and muons, which will permit to test the private Higgs hypothesis. At linear colliders it will be possible to measure these couplings with better precision; more recently there have appeared some claims that the coupling with strange quarks is also possible, both the flavor-conserving [139] and flavor-violating ones [140]. Furthermore, this could also be possible within the models with Higgs portal to dark matter, In such case, the direct detection of DM depends on the Higgs interaction with nucleons, which in turn depends on the Higgs coupling with light quarks.…”
Section: Discussionmentioning
confidence: 99%
“…In our model, the upper limits for the branching ratios of h → q i q j are predicted to decrease by 1 1+ 1 k times that of the predictions in [84,85]; for details see Table 1. The weakest constraints are in the b-s sector, Br(hbs) < 3.5 × 10 −3 , which is too small to be observed at the LHC because of the large QCD backgrounds, but these signals are expected to be observed at the ILC [94] in the future.…”
Section: (G − 2) μmentioning
confidence: 98%
“…[22,23]). Concerning flavor-changing couplings of h to other quarks, the LHC experiments have little direct sensitivity [24], while the ILC could in principle reach subpercent sensitivity for the branching ratios of h → bs, bd [25]; in Ref. [26], it was found that BR(h → bs) can be as large as 10 −1 in Two-Higgs-Doublet Models (2HDM).…”
Section: Contentsmentioning
confidence: 99%